Parian Polyandreia : the late geometric funerary legacy of cremated soldiers' bones on socio-political affairs and military organizational preparedness in ancient Greece /: the late geometric funerary legacy of cremated soldiers' bones on socio-political affairs and military organizational preparedness in ancient Greece. (2017) - Agelarakis, Anagnostis P, 1956-
No abstract available